Combining steady-state photo-capacitance spectra with first-principles calculations: the case of Fe and Ti in β-Ga2O3. (19th June 2020) - Zimmermann, C; Kalmann Frodason, Y; Rønning, V; Varley, J B; Vines, L
Abstract: In this study, we demonstrate an approach to identify defects in wide band gap semiconductors by comparing accumulatively-recorded derivative steady-state photo-capacitance (SSPC) spectra to simulations using results from first-principles calculations. Specifically, we present a method to simulate SSPC spectra which adopts inputs both from first-principles calculations and the experimental conditions. The applicability of the developed method is demonstrated using the cases of subsitutional Fe (FeGa ) and Ti (TiGa ) defects in β-Ga2 O3 . Using deep-level transient spectroscopy, we identify defect levels associated with Fe GaI 0 / − ( E A = 0.66 eV), Fe GaII 0 / − ( E A = 0.79 eV) and Ti GaII + / 0 ( E A = 1.03 eV) in the β-Ga2 O3 samples studied here. Accumulatively-recorded SSPC spectra reveal several defect levels labeled T 1 E F G – T 6 E F G with onsets for optical absorption between 1.5 eV and 4.3 eV. The signature T 1 E F G consists of several overlapping defect signatures, and is identified as being related to Fe GaI 0 / −, Fe GaII 0 / − and Ti GaII + / 0 by comparing measured and simulated accumulatively-recorded derivative SSPC spectra.